Responsible Business Model: A Corporate Social Responsibilitiy Aprproach to Business Model - Ansari, Manouchehr; Javaherian, Masoumeh (International Review of Management and Marketing, 2018)
Corporate contribution to social, environmental and economic concerns has been one of the pivotal issues for both businesses and society in recent years. Although many researchers have worked on this topic and established useful approaches which motivate companies and guide them to perform corporate social responsibility (CSR), there is still lack of applicable models that can help companies to accomplish CSR as part of their business model. The aim of this paper is to discuss how companies can integrate CSR into the business model in pursuit of creating Responsible Business Model. Responsible Business Model offers new ways and methods to create value for all stakeholders involved in a business including shareholders, society, employees, and so forth. Keywords: responsible business model, corporate social responsibility, business model, stakeholders. JEL Classification: M01